2003
DOI: 10.1128/jvi.77.19.10186-10201.2003
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Human Papillomavirus Productive Cycle during Neoplastic Progression Provides a Basis for Selection of Diagnostic Markers

Abstract: The productive cycle of human papillomaviruses (HPVs) can be divided into discrete phases. Cell proliferation and episomal maintenance in the lower epithelial layers are followed by genome amplification and the expression of capsid proteins. These events, which occur in all productive infections, can be distinguished by using antibodies to viral gene products or to surrogate markers of their expression. Here we have compared precancerous lesions caused by HPV type 16 (HPV16) with lesions caused by HPV types th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
222
1
17

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(251 citation statements)
references
References 83 publications
11
222
1
17
Order By: Relevance
“…The most probable explanation for this is the sampling strategy used (biopsies versus cervical scrapes). Although analyses of exfoliated cells enable an easy access to clinical material and are clearly ideal in a diagnostic setting the results are not representative for the overall quantity of the RNA or for the diversity of viral mRNA species in the underlying lesions (Middleton et al, 2003). Moreover, in our study we did not relate E6/E7 expression levels to viral genome copy number.…”
Section: Figurementioning
confidence: 68%
“…The most probable explanation for this is the sampling strategy used (biopsies versus cervical scrapes). Although analyses of exfoliated cells enable an easy access to clinical material and are clearly ideal in a diagnostic setting the results are not representative for the overall quantity of the RNA or for the diversity of viral mRNA species in the underlying lesions (Middleton et al, 2003). Moreover, in our study we did not relate E6/E7 expression levels to viral genome copy number.…”
Section: Figurementioning
confidence: 68%
“…The World Health Organization has officially designated HPVs -16 and -18 as carcinogenic agents. According to earlier information, and -82 were classified as "high-risk types" (Munoz et al, 2003;Bouvard et al, 2009), and associated with cervical cancer; while were classified as "low-risk types" (Middleton et al, 2003;Trottier and Burchell, 2009), which were found difficult for detection in cervical lesions but associated with anogenital warts.…”
Section: Introductionmentioning
confidence: 99%
“…One factor considered to be of key importance for the progression of intraepithelial lesions to invasive disease is integration of HPV into the host cell genome. 2,[7][8][9] The majority of CIN II/III lesions and all ICCs are infected with high risk (oncogenic) HPV types, particularly HPV 16 and 18. The E2 region of the HPV genome, which is involved in the regulation of the oncogenic HPV E6 and E7 proteins, is frequently disrupted when the virus is integrated.…”
mentioning
confidence: 99%